2022
DOI: 10.1007/s40520-022-02113-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 quarantine on cognitive, functional and neuropsychiatric symptoms in patients with mild cognitive impairment and dementia

Abstract: Background During the last two years, COVID-19 affected older people with dementia or mild cognitive impairment (MCI), but conflicting and sparse results are still present. The objective of this study was to investigate the frequency and type of changes in functional, cognitive and behavioral and psychological symptoms of dementia (BPSD), and caregiver’s stress during the period of quarantine in 2020 in patients affected by dementia/MCI living in Palermo, Sicily. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
15
0
3
Order By: Relevance
“…An important and less recognized, indirect consequence of the pandemic is that it has left many older people, including those with dementia, who are vulnerable to greater risk for severe illness from infection [ 18 ] restricted to home, with reduced opportunities and resources available to support their ongoing participation in physical activity or exercise in the community [ 19 ]. Ongoing impacts of this is the potential for increased risk for falls, a decline in their physical function and negative impact on the cognitive and neuropsychiatric symptoms of older people with dementia [ 20 ]. Therefore, an intervention designed to increase physical activity levels for people with dementia and address these challenges is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…An important and less recognized, indirect consequence of the pandemic is that it has left many older people, including those with dementia, who are vulnerable to greater risk for severe illness from infection [ 18 ] restricted to home, with reduced opportunities and resources available to support their ongoing participation in physical activity or exercise in the community [ 19 ]. Ongoing impacts of this is the potential for increased risk for falls, a decline in their physical function and negative impact on the cognitive and neuropsychiatric symptoms of older people with dementia [ 20 ]. Therefore, an intervention designed to increase physical activity levels for people with dementia and address these challenges is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[ 47 ]. During the long period (9 to 12 months), three studies reported a decrease in the patients’ overall cognitive status [ 27 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, there is still a paucity of prognostic tools based on CGA that evaluate the impact of COVID-19 in older subjects, even if some recent reports suggested that the impact of the COVID-19 pandemic on frailty condition is largely independent of the direct effect of the virus [ 33 ]. Consistently, growing evidence brings attention to the burden of the indirect effects of COVID-19 (i.e., psychological distress, cognitive impairment, malnutrition and physical inactivity), which are reflected in multidimensional well-being [ 34 ]. Therefore, it is reasonable to think, particularly during this pandemic, that only a CGA-based approach is qualified to really capture and track the changes in frailty condition.…”
Section: Discussionmentioning
confidence: 99%